2021
DOI: 10.1096/fj.202002061r
|View full text |Cite
|
Sign up to set email alerts
|

Downregulated ribosomal protein L39 inhibits trophoblast cell migration and invasion by targeting E‐cadherin in the placenta of patients with preeclampsia

Abstract: Early-onset preeclampsia (PE) is a pregnancy complication that can lead to severe adverse maternal and fetal outcomes. However, the mechanisms underlying the development of early-onset PE are not fully understood. Ribosomal protein L39 (RPL39) is a member of the S39E family of ribosomal proteins that plays an important role in stem cell self-renewal, cancer metastasis, and chemoresistance. In this study, we aimed to explore the potential function of RPL39 in placental trophoblast cells. We analyzed the express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…The in vitro experiments verified that tolcapone inhibits the migration and invasion of trophoblasts through changes in EMT signaling. Consistently, excessive E-cadherin hampered trophoblast invasion and has been implicated in patients with preeclampsia 25,26 . These findings suggest that tolcapone-induced productive and developmental toxicity share a similar mechanism of preeclampsia etiology.…”
Section: Discussionmentioning
confidence: 86%
“…The in vitro experiments verified that tolcapone inhibits the migration and invasion of trophoblasts through changes in EMT signaling. Consistently, excessive E-cadherin hampered trophoblast invasion and has been implicated in patients with preeclampsia 25,26 . These findings suggest that tolcapone-induced productive and developmental toxicity share a similar mechanism of preeclampsia etiology.…”
Section: Discussionmentioning
confidence: 86%
“…Ribosome biogenesis and translation were particularly critical for cell growth and proliferation (48). Jie et al (49) reported that knockdown of ribosomal protein L39 (RPL39) inhibited the proliferation, migration, and invasion of trophoblast cells in vitro. APO was closely related to abnormal biological function of trophoblasts, since trophoblast cells were vital to placental and fetus development (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that SLC6A9 [99], FKBP1B [100], S100A12 [101], SLC6A19 [102], TXN (thioredoxin) [103], TLR9 [104], HP (haptoglobin) [105], ARG1 [106], PINK1 [107], B2M [108], C5AR1 [109], MYADM (myeloid associated differentiation marker) [110], CBS (cystathionine beta-synthase) [111], GPX1 [112], SIAH2 [113], PRDX2 [114], RDH8 [115], CYP11B2 [116], RARRES2 [117], NOX1 [118], IL33 [119], OTC (ornithine transcarbamylase) [120], CYP1A1 [121], NFATC4 [122], TSLP (thymic stromal lymphopoietin) [123], WNT4 [124], MGP (matrix Gla protein) [125], FGFBP1 [126], GHR (growth hormone receptor) [127], ERBB3 [128], GFAP (glial fibrillary acidic protein) [129], CCDC40 [130], CACNB2 [131], CD34 [132], NOTCH3 [133], TERT (telomerase reverse transcriptase) [134], GNB3 [135], TP73 [136], RYR2 [137], ENPEP (glutamyl aminopeptidase) [138], SCN7A [139], WNK4 [140], SFRP5 [141], GDF15 [142], CAV1 [143], KCNA5 [144], FOXC1 [145], ASIC1 [146], VASH2 [147], CXCL8 [148], PAPPA2 [149], KCNMA1 [150], LOX (lysyl oxidase) [151], SPARCL1 [152] and CYP3A5 [153] might have the potential to be used as diagnostic biomarkers of hypertension. Previous studies have reported that RHD (Rh blood group D antigen) [154], S100A12 [155], TXN (thioredoxin) [156], TLR9 [157], S100P [158], TAGLN2 [159], S100A9 [160], CA1 [161], HP (haptoglobin) [162], RPL39 [163], F5 [164], PINK1 [165], B2M [166], S100A11 [167], SLC4A1 [168], CBS (cystathionine beta-sy...…”
Section: Discussionmentioning
confidence: 99%